2018
DOI: 10.1039/c8nr00934a
|View full text |Cite
|
Sign up to set email alerts
|

Marrying SPR excitation and metal–support interactions: unravelling the contribution of active surface species in plasmonic catalysis

Abstract: Plasmonic catalysis takes advantage of the surface plasmon resonance (SPR) excitation to drive or accelerate chemical transformations. In addition to the plasmonic component, the control over metal-support interactions in these catalysts is expected to strongly influence the performances. For example, CeO2 has been widely employed towards oxidation reactions due to its oxygen mobility and storage properties, which allow for the formation of Ce3+ sites and adsorbed oxygen species from metal-support interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…It can be observed that CeO2 samples absorb light in the near-visible UV (<450 nm) [8]. Upon Au deposition, a band in the visible (≈550 nm) appears due to the LSPR dipolar mode in Au NPs [8,12]. Raman and XPS spectroscopies were employed to probe the metal-support interactions and oxygen vacancy properties in CeO2 and Au/CeO2 nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be observed that CeO2 samples absorb light in the near-visible UV (<450 nm) [8]. Upon Au deposition, a band in the visible (≈550 nm) appears due to the LSPR dipolar mode in Au NPs [8,12]. Raman and XPS spectroscopies were employed to probe the metal-support interactions and oxygen vacancy properties in CeO2 and Au/CeO2 nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that CeO 2 samples absorb light in the near-visible UV (<450 nm) [ 8 ]. Upon Au deposition, a band in the visible (≈550 nm) appears due to the LSPR dipolar mode in Au NPs [ 8 , 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Camargo's group, on the other hand, showed the tuning of activity and selectivity of plasmonic gold nanoparticles for organic transformations by the concept of hybrid materials and metal-support interactions. [10][11][12] Tuning the LSPR of the material to optimize the electromagnetic (EM) and thermal hotspots has scientic and technological advantages. Plasmonic coupling, a near-eld coupling of the dipoles in the presence of light, can also be tuned by modifying the gap/distance between NPs.…”
Section: Introductionmentioning
confidence: 99%
“…The gold nanourchins, nanodendrites, and nanospheres were impregnated on commercial SiO2 by the incipient wetness impregnation method. 42 For this procedure, the suspension of each nanostructure was batched synthesized (an appropriated amount to obtain 300 mg 2 wt.% Au/SiO2) and concentrated in 5 mL of ethanol. The commercial SiO2…”
Section: Synthesis Of Au/sio2 Materialsmentioning
confidence: 99%